Thai Consumers’ Perception on Herbal Cosmetic Products: A Comparative Study of Thai and Imported Products - Thanisorn, Rojanadilok; ., Bunchapattanasakda Chanchai (Information Management and Business Review, 2012)
This research investigated the factors that influence perception of Thai consumers on facial herbal cosmetic products in Thailand. In- depth interview the perception of Thai consumers was utilized in data collection, while content analysis was employed in data analysis. The facial herbal cosmetics products are moisturizer, whitening lotions, creams, powder, toner, make up cleansing, mask, cleansing oil, soap bar, anti-aging lotions and creams. This study revealed that most of the interviewees were female with age between 26-30 years, casual worker ,bachelor degree being the highest education and salary from 10,000 -15,000 baht (285-430) per month. The marketing mix (4Ps: product, price, place and promotion) were the key factors influencing Thai consumers’ perception on facial herbal cosmetic products. The result found that Thai consumers were satisfied with physical appearance of products; texture, odor, penetration- characteristic and viscosity. Thai consumers trust in the safety of the Thai and imported products. The imported products have new manufacturing technologies of production compare with the Thai products but imported products are more expensive than Thai products. Thai consumers were satisfied with packaging design and pump bottle shape of imported products. Thai consumers found it was convenience to purchasing both herbal products from department store. The direct sale is popular only for Thai products. The imported products had more interesting marketing promotion than the Thai products. The marketing promotions are new product premium, promotion campaign eg. Cash discount, gift premium, fortune, tarot horoscope, makes up and massage workshop. Thai consumers were satisfied with advertisement of both herbal products; brochure, leaflet, beauty information from general magazine, fashion magazine, general book, television and radio. The economic situation, such as inflation situation, is the majority factor of purchasing decision. The average cosmetic budget per each purchase is 1,800 baht (about 50) at the rate of eight purchases per year.